LEGAL PROTECTION OF THE MORAL RIGHTS OF NOVEL AUTHORS ON ONLINE PLATFORMS (World Bulletin of Management and Law, 2023)
Novels published on online platforms are one of the copyrighted works that are quite widely violated by copyright, both economic and moral rights. The purpose of this study is to analyze the form of handling violations of the moral rights of novel authors on online platforms and to analyze the form of legal protection of the moral rights of novel authors on online platforms in the Copyright Law 2014. This study used normative juridical research methods. The results of research, handling or law enforcement against violations of the moral rights of novel authors are influenced by elements in the legal system, namely law enforcement, regulations governing moral rights in copyright, and culture or legal awareness of the community. Preventive Legal Protection of the moral rights of novel authors is regulated in the Copyright Law of 2014, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, and Circular Letter of the Minister of Communication and Information Number 5 of 2016. Repressive Legal Protection, sought in the event of a dispute over violations of moral rights, with settlement through non-litigation and litigation.